1979
DOI: 10.1111/j.1528-1157.1979.tb04799.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Stimulation in Alumina‐Gel Monkey Model: Inverse Relationship Between Clinical Seizures and EEG Interictal Bursts

Abstract: The efficacy of cerebellar stimulation was addressed in a chronic monkey model (N = 12) of spontaneous focal motor and secondarily generalized seizures using 24 hr seizure frequency monitoring and all-night EEG recording. The anterior cerebellar vermis was stimulated employing parameters similar to those used in man, 10 Hz, 1 msec pulses, 10 min on, 10 off, at an average current of 2.0 mA. Six weeks pre- and post-base-line periods were compared to a stimulation period of the same length. The results contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…Numerous animal studies have demonstrated that electrical stimulation of the cerebellum may abort electrically or chemically induced seizures and drastically alter the electrophysiological profile of the neuronal tissue in vitro and in vivo. 1,2,5,8,[13][14][15]19,21,22,26,28,30,35,38,39,41,42,48,49,52,53 However, there are several issues that remain to be resolved and important questions that need to be answered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous animal studies have demonstrated that electrical stimulation of the cerebellum may abort electrically or chemically induced seizures and drastically alter the electrophysiological profile of the neuronal tissue in vitro and in vivo. 1,2,5,8,[13][14][15]19,21,22,26,28,30,35,38,39,41,42,48,49,52,53 However, there are several issues that remain to be resolved and important questions that need to be answered.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of the animal experimental studies but also the clinical trials have used the cerebellum cortical surface as stimulation target, with frequently contradictory results. 8,5,[14][15][16]22,23,38,48,52,53 However, the stimulation of the deep cerebellar nuclei appears to provide more solid data and better seizure control. 1,35 There are several mechanisms that may explain this discrepancy in the results of the cortical CS in animal and human studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, cerebellar stimulation increased seizure threshold in the rabbit following PTZ administration but not in the electrical stimulation induced seizure model (17). In a chronic epilepsy monkey model, anterior cerebellar vermis stimulation using parameters analogous to Cooper worsened seizure frequency (18). Reimer and colleagues described the effects of cerebellar stimulation on cobalt experimental epilepsy in the cat (19).…”
Section: Deep Brain Stimulation Of the Epilepsy Control Systemsmentioning
confidence: 99%
“…Moruzzi und Magoun fanden eine Verminderung der Dezerebrationsstarre bei Ratten durch Hochfrequenzstimulation des Kleinhirns [76]. Daraufhin wurden in verschiedenen Institutionen Tierversuche zur Anfallskontrolle durch Kleinhirnstimulation durchgeführt, die sowohl positive [5,42,51] als auch negative [47,62,79] Ergebnisse brachten. Cooper et alversuchten schließ-lich 1970, menschliche Anfälle mit Kleinhirnstimulation zu behandeln und berichteten über Anfallsfreiheit bei 27% der Probanden in unkontrollierten Fallserien [27,28,29].Diese Resultate konnten jedoch in doppelblind kontrollierten Studien [110,127] nicht bestätigt werden.…”
unclassified